EFEKTIVITAS SENAM KAKI DIABETUS MELITUS TERHADAP STATUS SIRKULASI PERIFER PADA PASIEN DIABETUS MELITUS - S.Kep., Ns., M.Kes, Diyono,; , A.,M.Kes, Ratna Indriati (Intan Husada : Jurnal Ilmiah Keperawatan, 2015)
Background. The  main  factors  that  prompted  researchers  doing this  study  is  because  more and  more  patients  diabetus  mellitus  (DM)  with  complications  of  leg  ulcers  and  even  some who  have  to  be  amputated  fingers  or  toes.  DM  patients  in  Indonesia  is  predicted  to  rise further, so that the risk of foot ulcers will also be greater. Is a complication of diabetes foot ulcers  due  to  neuropathy  and  angiopathy,  which  basically  can  be  prevented  with  good  foot care.  This  study  sought  to  find  or  prove  the  effectiveness  of  DM  leg  exercises  to  improve peripheral circulation in patients diabetus mellitus.Objective: the  purpose  of  this  study  was  to  assess  the  effectiveness  of  DM  leg  exercises  to increase the status of the peripheral circulation in patients diabetus mellitus Method. This research is a Quasi Experiment with the design of one group pre test post test. The study population was patients with Diabetes Mellitus there Joho, Pracimantoro Wonogiri by 30 respondents. The sampling technique used is total sampling (sampling saturated). Data were analyzed using paired t test  with SPSS for windows 16 series. Result.  Women  respondents  were  19  (63.33%)  and  male  respondents  as  many  as  11 respondents  (36.67%).  Before  the  DM  leg  exercises,  all  respondents  were  30  or  100% indicates  the  status  of  the  peripheral  circulation  in  grades  0-4  or  bad  category.  Status peripheral  circulation  in  diabetic  patients  after  DM  foot  gymnastics  in  grades  0-4  (bad) as much as 4 respondents or 13.3%, while for grades 5-6 (good) by 26 or 86.7% .Value average peripheral circulatory status after DM foot gymnastics is 5.17 better than before performing leg exercises with value is 2,53Conclusion: Gymnastics  feet  DM  is  effective  to  improve  the  status  of  the  peripheral circulation  in  diabetic  patients  with  statistical test  results  Dependent  paired  t  test  (t  test) obtained p value: 0.00 (p <0.05)Keywords: Gymnastics feet DM, peripheral circulation, Diabetus Mellitus